061 An exploration of a clinical decision support system for perfusionists. (December 2018) - Adekoya, T; Rogers, Y; Issitt, R; Sebire, N
Abstract : Introduction: Studies on clinical decision support systems have largely concentrated on drug prescribing, however, there are additional use cases which the systems could be used for, such as the area of perfusion where little research currently exists and is mainly focused on image interpretation. Therefore, this study aimed to investigate how clinical decision support systems could support perfusionists and the requirements needed in order to build a prototype through participatory design. Methods: The investigation took a grounded theory approach, using a mixed method of contextual inquiries and semi-structured interviews with senior perfusionists, to develop theories based on the context of their work. A thematic analysis was then used to analyse the findings and 4 use cases were discovered. One of the use cases was then investigated further and participatory design was used to gather the requirements, this involved interviews and the review of a paper prototype to validate and further refine the requirements. Results: The findings resulted in the development of a RShiny application which predicts which heart-lung machine equipment will be required for an operation based on a patient's body surface area. The app achieves this by calculating the patient's body surface area from the height and weight inputted by the user and querying a table for the corresponding equipment, which was based on a clinical guideline table provided by the perfusionists. Discussion: User testing found that the app was intuitive and user friendly, although it still required added functionality and lacked data validation. Nevertheless it successfully automated a task that the perfusionists manually perform regularly. The study concluded that there is a large opportunity for clinical decision support systems to be used in the area of perfusion and that contextual inquiries and participatory design can be used as effective tools to gather accurate requirements for such systems.